The Feel4Diabetes intervention: effectiveness on 24-hour physical behaviour composition in families at risk for diabetes development. (26th October 2022) - Cardon, Greet; Chastin, Sebastien; Van Stappen, Vicky; Huys, Nele; Stefanova, Tanya; Chakarova, Nevena; Kivelä, Jemina; Alberto Moreno, Luis; Sándor Istvánné, Radó; Androutsos, Odysseas; Manios, Yannis; De Craemer, Marieke
Summary: The Feel4Diabetes project conducted a 2-year intervention aiming to encourage healthy behaviours in families in six European countries. Within this paper, the intervention effect was evaluated after the first intervention year on 24-hour physical behaviour composition in Belgian families at risk for type 2 diabetes. Parents' and children's levels of physical activity (PA) and sedentary behaviour (SB) were objectively measured and sleep duration was self-reported. Valid data were obtained in 82 children (mean age: 8.2 ± 0.84; 50.0% boys) and 72 parents (mean age: 40.1 ± 5.5; 27.8% fathers). Data were analysed using a compositional data approach, and mixed models were used to take clustering into account. Results showed that for children, the mean baseline composition of the 24-hour day in sleep, SB, light and moderate-to-vigorous PA for the intervention group was (11 hours 18 minutes; 6 hours 33 minutes; 5 hours 02 minutes, 1 hour 08 minutes) and for the control group (11 hours 18 minutes; 6 hours 35 minutes; 5 hours 04 minutes; 1 hour 06 minutes), respectively. For parents, the mean baseline composition was for the intervention group (8 hours 12 minutes; 9 hours 36 minutes; 5 hours 43 minutes; 27 minutes) and for the control group (8 hours 00 minute; 9 hours 00 minute; 6 hours 27 minutes; 33 minutes). No significant intervention effects were found on 24-hour physical behaviour composition of either parents or children ( p = 0.19 and p = 0.21, respectively). A relatively small study population and a poor attendance rate among parents could maybe explain the lack of effectiveness. More effective strategies are needed to retain vulnerable families in interventions. Furthermore, future approaches to improve the 24-hour physical behaviour composition should maybe focus more specifically on PA, SB and sleep, and involve teachers, children and parents in the design of the intervention. Trial registration: NCT02393872 in ClinicalTrials.gov.